Blockchain and Hadoop Integrated Platform - Chang, Bryan Jie Ming (IRC, 2019)
The explosion of Bitcoin has drawn the world’s attention towards the field of blockchain. This has driven studies and applications towards finding more new possibilities and usage of blockchain. However, currently there is no blockchain framework that can perform data analytics for itself. On the other hand, big data too is an emerging technology that analyze huge amount of data and is gaining attention to organizations since the world is producing more data each day. Data is the new oil and with proper processing, it can provide huge benefits to the companies to better insights and planning. This study will highlight the integration among Hadoop and blockchain, and emphasizes on how and why blockchain can complement with Hadoop’s Eco-systems and their pros and cons.